Pengaruh Entrepreneurial Orientation dan Market Orientation Terhadap Business Performance yang Dimediasi oleh Marketing Capabillity pada UMKM Kuliner di Kota Sukabumi - Fani Julia Pratama; R. Deni Muhammad Danial; Resa Nurmala (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
One industry that is growing and in the spotlight is the food and beverage industry sector, where the sector is known to be a shining warabala sector and will continue to move to improve. The purpose of this study was to determine the effect of entrepreneurial orientation, market orientation on business performance and to determine marketing capability in mediating the relationship between entrepreneurial orientation, market orientation on business performance in MSMEs in Sukabumi. The methods used in this study are descriptive and associative methods through a quantitative approach. The population in this study were culinary MSME players in the city of Sukabumi. The sample used in this study amounted to 270 culinary umkm in the city of Sukabumi based on the theory of Hair Jr. The research data used in this study include primary data and secondary data, namely observation, interviews, questionnaires, literature studies, and documentation. The results of this study are that there is a positive and significant influence between entrepreneurial orientation and market orientation on business performance and marketing capability as a mediator plays an important role in the relationship between entrepreneurial orientation and market orientation with business performance.